Pengembangan Bahan Ajar Berbasis E-Book Menggunakan Flip Pdf Professional pada Mata Pelajaran Sejarah Kebudayaan Islam - Munfarida, Atik; Fitri, Agus Zaenul (Fakultas Tarbiyah IAI Nasional Laa Rooiba, 2024)
This research is motivated by the importance of developing E-book-based teaching materials in SKI lessons, because these lessons make students bored and less interesting. This study aims to determine the application of E-book teaching materials using Flip PDF Professional in Islamic cultural history subjects, and the effectiveness of E-book teaching materials using Flip PDF Professional in Islamic cultural history subjects. This research uses research and development. The sample in this study was using class X students at MAN 1 Trenggalek with a non-probability sampling technique. Data collection techniques and instruments used tests, distribution of e-book products, questionnaires or questionnaires, interviews, and documentation. Data analysis used the effectiveness test through the normality test and the assumption test using the paired t test and two independent samples (parametric). The results showed that the development of Flip PDF Professional teaching materials was carried out with reference to the development and research of ADDIE Analysis, Design, Development, Implementation, evaluation. Material development shows that the student learning outcomes for the experimental class posttest and the control class posttest have significant differences, thus the e-book teaching materials using Flip PDF Professional are effective in the subject of Islamic cultural history. Keywords: Development, E-book Based Teaching Materials, Flip Pdf Professional, Islamic Cultural History Subject.